Pengaruh Edukasi Audiovisual Pasien Pasca Operasi Strabismus Terhadap Kemampuan Koordinasi Penglihatan - Rosaliana Ayu Saputri; Muhammad Hadi; Naryati Naryati; Tini Suminarti (Universitas Malahayati, 2026)
ABSTRACT Strabismus, commonly known as crossed eyes, is a condition in which both eyes are misaligned when focusing on the same object. One or both eyes may deviate inward (esotropia), outward (exotropia), upward (hypertropia), or downward (hypotropia). This condition results from an imbalance in the neuromuscular system that controls eye movement, impaired brain-eye coordination, and abnormal binocular vision. This study aims to analyze the effect of audiovisual-based education on visual coordination in patients after strabismus surgery. The study employs theGeneralized Linear Model Repeated Measure (GLM-RM) method to examine differences in the effects of audiovisual education between the intervention and control groups. Results: The GLM-RM analysis indicated a significant difference between the intervention and control groups after receiving audiovisual education, with a mean difference of 97.78 and a p-value of 0.000. The Greenhouse-Geisser test showed a significance value of 0.000, while the test of between-subjects effects revealed a statistically significant difference between the two groups (p-value = 0.000). Additionally, the parameter estimates test confirmed a significant effect of audiovisual education on patients’ visual coordination over time (p-value = 0.000). Conclusion: Audiovisual-based education has a significant positive impact on improving visual coordination in patients following strabismus surgery. Keywords: Audiovisual Education, Visual Coordination, Strabismus. ABSTRAK Strabismus atau mata juling merupakan kondisi di mana kedua mata tidak sejajar saat melihat suatu objek. Salah satu atau kedua mata dapat mengalami deviasi ke dalam (esotropia), ke luar (eksotropia), ke atas (hipertropia), atau ke bawah (hipotropia). Kondisi ini disebabkan oleh ketidakseimbangan sistem neuromuskular yang mengatur pergerakan bola mata, gangguan koordinasi otak dan mata, serta kelainan penglihatan binokular. Penelitian ini bertujuan untuk menganalisis pengaruh edukasi berbasis audiovisual terhadap koordinasi penglihatan pada pasien pascaoperasi strabismus. Desain penelitian ini menggunakan metode Generalized Linear Model Repeated Measure (GLM-RM) untuk menganalisis perbedaan efek edukasi audiovisual antara kelompok kontrol dan intervensi. Hasil analisis GLM-RM menunjukkan adanya perbedaan yang signifikan antara kelompok intervensi dan kontrol setelah diberikan edukasi audiovisual, dengan nilai mean difference = 97,78 dan p-value = 0,000. Uji Greenhouse-Geisser menunjukkan signifikansi sebesar 0,000, sedangkan uji test of between-subjects effects mengindikasikan adanya perbedaan signifikan antara kedua kelompok dengan p-value = 0,000. Selain itu, berdasarkan uji parameter estimates, terdapat perbedaan yang signifikan dalam pengaruh edukasi audiovisual terhadap koordinasi penglihatan pasien pascaoperasi dari waktu ke waktu (p-value = 0,000). Edukasi berbasis audiovisual berpengaruh secara signifikan dalam meningkatkan koordinasi penglihatan pasien setelah menjalani operasi strabismus. Kata Kunci: Edukasi Audiovisual, Koordinasi Penglihatan, Strabismus.